Franz Brentano und sein philosophischer Nachlass - Binder, Thomas (De Gruyter, 2019)
The monograph tries to throw new light on Franz Brentanos (1838-1917) conspicuous reluctance to publish his philosophical findings based on his biography, personality and the development of his scientific theories. In addition to that the book presents the difficult history of Brentano's extensive philosophical Nachlass until the immediate present.